2018
DOI: 10.3892/mco.2018.1727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neutrophil‑to‑lymphocyte ratio and calcitonin concentration for predicting lymph node metastasis and distant metastasis in patients with medullary thyroid cancer

Abstract: The aim of the present study was to investigate potential predictive factors of lymph node metastasis (LNM) and distant metastasis (DM) of medullary thyroid cancer (MTC). A total of 61 patients newly diagnosed with MTC at the General Hospital of the Chinese People's Liberation Army between January 2001 and January 2016 were enrolled and divided into two groups according to the results of preoperative examinations and surgical histopathology as follows: Group NM (without metastases), and group M (with metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Preoperative NLR was not associated with clinicopathological characteristics in PTC patients [159,160]. By contrast, other studies reported that the preoperative NRL was correlated with the size and lymph node metastasis of PTC patients [161,162,163,164]. In conclusion, the diagnostic and prognostic significance of NLR in different types of TC remains uncertain.…”
Section: The Immune Landscape In Tcmentioning
confidence: 82%
“…Preoperative NLR was not associated with clinicopathological characteristics in PTC patients [159,160]. By contrast, other studies reported that the preoperative NRL was correlated with the size and lymph node metastasis of PTC patients [161,162,163,164]. In conclusion, the diagnostic and prognostic significance of NLR in different types of TC remains uncertain.…”
Section: The Immune Landscape In Tcmentioning
confidence: 82%
“…Recent studies have demonstrated that the NLR represents the balance between antitumor immune function and the inflammatory response [41]. Increased preoperative NLR was associated with lymph node metastasis and distant metastasis [42] as well as treatment resistance [43]. We suspect that the postNLR may play an important role in the activation of micrometastases and resistance to treatment.…”
Section: Plos Onementioning
confidence: 95%
“…The accuracy of NLR for different cut-off values is given in Table 3. Elevated preoperative NLR has been shown to be related with incomplete response to therapy [22], poor tumor differentiation [23], lymph node invasion [24], advanced stage [25] and higher thyroglobulin values [26] in thyroid malignancies. On the other hand, in 2016, a meta-analysis of 6 prospective cohorts with 6283 differentiated thyroid cancer patients revealed no difference in NLR 6 between patients with cancer and benign nodules with a mean difference of 0.19 (95% CI: -0.09-0.46, p<0.001).…”
Section: Resultsmentioning
confidence: 99%